2013
DOI: 10.11118/actaun201260050181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fertilization and harvest frequency on floristic composition and yields of meadow stand

Abstract: The effect of fertilization and the harvest frequency on production and floristic characteristics of a meadow stand were assessed in a small plot trial established in 2003 in Vatín, Vysočina Region, the Czech Republic. Four levels of fertilization (none; N0 + P30 + K60 kg∙ha−1; N90 + P30 + K60 kg∙ha−1; N180 + P30 + K60 kg∙ha−1) were combined with four treatments of exploitation intensity (4 cuts per year, first cut on 15th May, every next after 45 days; 3 cuts per year, first cut on 30th May, every next after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…On average, the pig slurry is twice as rich in the content of phosphorous as the cattle slurry (Regulation No. 274/1998 of the Ministry of Agriculture), whereas phosphorus has a positive influence on legumes dominance in grasslands as it was proved by studies such as Skládanka and Hrabě (2008), Veselá et al (2009) or Raus et al (2012).…”
Section: Functional Groupsmentioning
confidence: 87%
“…On average, the pig slurry is twice as rich in the content of phosphorous as the cattle slurry (Regulation No. 274/1998 of the Ministry of Agriculture), whereas phosphorus has a positive influence on legumes dominance in grasslands as it was proved by studies such as Skládanka and Hrabě (2008), Veselá et al (2009) or Raus et al (2012).…”
Section: Functional Groupsmentioning
confidence: 87%
“…Extensive harvest pattern supports the dominance of valuable species, yet at the same time the herbage is harvested too late in its inappropriate phenological phase. Raus et al (2012) reported that higher number of mowings per year caused expansion of grasses at the expense of non-leguminous forbs which are generally found less valuable. There were also detected some shi s within the group of grasses.…”
Section: : Simpson Diversity Index (Sim) In Relation To Cutting Patmentioning
confidence: 99%
“…In contrast, [19] found that the percentage of legumes in grassland increased with greater application rate of swine slurry. The reason for this finding could be that pig slurry supplies more phosphorus has a positive effect on legume dominance in grasslands as has been reported by [20,21,22].…”
Section: Floristic Compositionmentioning
confidence: 56%